Evaluation of factors influencing bank operating efficiency in Tanzanian banking sector - Josephat Lotto (Cogent Economics & Finance, 2019)
This paper examines factors affecting operating efficiency of 36 commercial banks in Tanzania for the period between 2000 and 2017. The paper employs robust random-effect regression model to estimate the relationship between bank operating efficiency and its determinants. The results show that bank liquidity and capital adequacy have a positive relationship with bank operating efficiency. This suggests that capital adequacy and liquidity, not only strengthen financial stability by providing a larger capital cushion and bank required liquidity level, but also improve bank operating efficiency by lowering moral hazard between shareholders and debt-holders. Furthermore, the study shows that bank profitability and operating efficiency are directly related-implying that banks should put emphasis on improving their earning generating power to increase their operational efficiency. This paper suggests banks to increase their profitability by investing more on financial innovations and branch networks, and expand their market shares to boost their operational efficiency. Further, the paper argues that banks should optimally use their asset capacity to enhance their earnings profiles. At the same time, banks should avoid reckless lending that would increase the level of unsecured credits in banks' portfolio. Finally, the results encourage banks in Tanzania to monitor and evaluate these factors for improvement to enable the sustainability of banks and industry for economic growth.
Keywords: 330; Commercial banks; operating efficiency; evaluation; profitability; liquidity; capital adequacy